Towards space science education: A study of students’ perceptions of the role and value of a space science program - Afful, Andoh Michael; Hamilton, Margaret; Kootsookos, Alex (Acta astronautica, 2020)
The field of Space has become very important in the wake of opportunities and strategic advantages accrued from it. It has become increasingly evident that space science education is beginning to gain grounds in the 21st century and it is perceived to bring about Science, Technology, Engineering, Mathematics (STEM) awareness providing a context for teaching and learning of the subject. The competitive nature of Space means developing nations will need to invest in the skills that the industry needs by way of sustained pathways, incentivised research and development, and assured a favourable prevailing business environment by way of creating capacities and capabilities in space sciences. Through an explanatory study, we draw on students’ responses (N = 504, interviews = 20) to investigate the educational need of a space science program. Findings revealed implications for the quality and function of a space science program which provide a platform for engagement in space related research and development. Data also demonstrated key facts with the potential of increasing the future of space science instruction which will necessitate a paradigm shift towards the value of space education in the phase of integrating a space science program in the curriculum. The paper concludes with recommendations for practitioners responsible for integration of new curriculum in science education in higher education sectors. •Positive student perceptions towards a space science program.•Space science education influences learners' decision in STEM studies.•Overwhelming student interest for space science curriculum integration.•Space science provides an interdisciplinary avenue for engagement and participation.•Positive mindset breeds right mentality to teaching and learning of the space science.